Effects of adiabatic focusing and free-escape boundaries in coronal shock acceleration - Annie John, Lidiya; Nyberg, Seve; Vuorinen, Laura; Vainio, Rami; Afanasiev, Alexandr; Poedts, Stefaan; Wijsen, Nicolas (EDP Sciences, 2025)
Solar energetic particles (SEPs) are considered a serious radiation threat to space technologies and 11 humans in space. SEPs are accelerated to high energies by solar explosive phenomena such as 12 solar flares and in particular by shocks driven by coronal mass ejections (CMEs). We aim to better 13 understand the effects of magnetic field gradient-induced adiabatic focusing on the coronal accel14 eration of SEPs and to test whether free-escape boundaries produce the same effects as focusing. 15 We present results from a one-dimensional oblique shock model with a mean free path similar to 16 Bell’s (1978) theory using Monte Carlo simulations. We show that the momentum spectrum at a 17 shock and far upstream will attain a steady state in a model with adiabatic focusing, whereas it 18 does not in a non-focusing model. However, the effects of focusing can be mimicked in a non19 focused simulation by introducing a free-escape boundary ahead of the shock close to the position 20 where the particles will escape from the shock by focusing in a focused transport simulation. This 21 provides a promising avenue for constructing computationally efficient codes that can model the 22 particle emission from shocks